2015
DOI: 10.1155/2015/840542
|View full text |Cite
|
Sign up to set email alerts
|

Novel Investigations of Flavonoids as Chemopreventive Agents for Hepatocellular Carcinoma

Abstract: We would like to highlight the application of natural products to hepatocellular carcinoma (HCC). We will focus on the natural products known as flavonoids, which target this disease at different stages of hepatocarcinogenesis. In spite of the use of chemotherapy and radiotherapy in treating HCC, patients with HCC still face poor prognosis because of the nature of multidrug resistance and toxicity derived from chemotherapy and radiotherapy. Flavonoids can be found in many vegetables, fruits, and herbal medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 240 publications
(279 reference statements)
0
37
0
Order By: Relevance
“…Cytokines, chemokines, pH value, hypoxia, fibroblast and extracellular matrix proteins are important components of the tumor microenvironment[18-21]. The tumor microenvironment plays an important role in regulating tumor progression[22,23]. It has been reported that many extracellular matrix proteins exert significant influence on tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines, chemokines, pH value, hypoxia, fibroblast and extracellular matrix proteins are important components of the tumor microenvironment[18-21]. The tumor microenvironment plays an important role in regulating tumor progression[22,23]. It has been reported that many extracellular matrix proteins exert significant influence on tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are safe and reliable agents that are extracted from natural products, which show a broad spectrum of biological activities with fewer side effects[116]. Phloretin is a natural phenol which could be extracted from manchurian apricot and apple tree leaves.…”
Section: Regulatory Mechanism Of Glucose Metabolic Reprogrammingmentioning
confidence: 99%
“…to suppress HCC proliferation, survival, and metastasis through induction of apoptosis and inhibition of signaling transduction which participates in tumor progression (7)(8)(9). In addition, some studies reported herbal medicine combined with chemotherapy to improve survival and tumor response compared to chemotherapy alone in the treatment of patients with HCC (10).…”
mentioning
confidence: 99%